Contrasting canopy and fibrous root damage on Swingle citrumelo caused by 'Candidatus Liberibacter asiaticus' and Phytophthora nicotianae. (15th May 2017) - Wu, J.; Johnson, E. G.; Gerberich, K. M.; Bright, D. B.; Graham, J. H.
Abstract : Huanglongbing (HLB), associated with the phloem‐limited bacterium ' Candidatus Liberibacter asiaticus' (Las), is devastating trees in citrus orchards of Florida. Additionally, Phytophthora nicotianae, omnipresent in citrus soils, causes root rot that reduces water and nutrient uptake by fibrous roots. To investigate fibrous root damage and replacement and canopy size in relation to infection of fibrous roots by Las and P. nicotianae, rootstock seedlings of Swingle citrumelo ( Citrus paradisi × Poncirus trifoliata ) were inoculated with Las or P. nicotianae in two greenhouse pot trials. Phytophthora nicotianae caused root damage within 5 weeks post‐inoculation, which led to greater reduction of canopy size than for Las‐infected seedlings by the end of the experiment. Las increased accumulation of fibrous root biomass at 5 weeks post‐root trimming (wpt) in the 2014 trial and at 11 wpt in the 2015 trial. New root length was not consistently increased by Las. Reduced total leaf area of symptomless Las‐infected seedlings compared to noninoculated controls might be due to the combined effect of altered carbohydrate allocation between shoots and roots and altered leaf morphology.